Ikhtiar Perbankan Syariah di Indonesia - Ahmad Afif (Fakultas Ekonomi dan Bisnis Islam, 2017)
The sharia economic movement in Indonesia has emerged formally in 1991 with the founding of Bank Muamalat initiated by ICMI. As part of the activists and founding fathers of the sharia economic movement that is now constantly endemic. Bank Muamalat has a direct influence on practitioners, academics and student and community movements. The establishment of Bank Muamalat hinted that this stage of Islamic economic da’wah has declared itself to be an open movement. At the same time entering the service stage of proof system that is considered as a solve of the capitalist system that until now does not lead to equitable prosperity, the distribution of unfair wealth, and the width of socio-economic disparities of society. Furthermore, in addition to the banks followed also various other financial institutions such as insurance, pawnshops, money market, capital markets or cooperative that is sharia